Der Liebhaber und die Geliebte: Geschlecht und Sprache im Bereich privater Lebensformen - Christen, Helen (My University, 2000)
The Swiss national Science Foundation is currently supporting a study which examines the linguistic consequences of changes in the structure of families. One of the questions concerns the way in which the factor gender proves to be relevant. In this article the fields of the naming of a child, terms of address and sex-specific designations for persons are taken as examples to outline connections emerging between language and sex.